Theoretical aspects of innovative capacity (Journal of Economic Research & Business Administration, 2019)
At the present stage of the Kazakh economy, the introduction and development of innovations is not only an important factor in improving the efficiency of enterprises, but also a priority area of national state economic policy.It should be noted that despite the presence in the country of significant fundamental and technological reserves, a unique scientific and industrial base, highly qualified personnel, there is a decrease in the efficiency of enterprises functioning due to the lack of own funds, limited financial resources andincreasing competition.The trends in the formation of post-industrial space dictate the need to find ways to develop andgrow the resource component of production. Many researchers on the issues of management and developmentof the innovation potential of enterprises see it as a key element in building a multifaceted,complex and sustainable structure. Innovation as a concept is actively developing among economists,theorists, researchers, and among industrialists, politicians, representatives of the business elite.The purpose of this study is to examine the theoretical aspects of the innovative potential of theenterprise, its essence, structure. The authors used the methods of complex analysis based on the systematizationand structuring of thematic material: compilative, systematic, statistical and analytical approaches.The authors have made conclusions regarding the nature and characteristics of the innovativepotential of the enterprise, the possibility of choosing the most objective method for evaluating the innovativepotential, based on the “basic” level of indicators, the relative value of which will determine thequalitative value of the actual value. The value of the conducted research in practical application is thepossibility of choosing the most objective method for assessing the innovative potential of an enterprisefrom those presented in the article.